Letter from Georg Bredig to Max Bredig, July 5, 1936 - Bredig, Georg (1936)
Georg Bredig (1868-1944) inquires about the well-being of his son, Max Bredig (1902-1977), after Max's return to Berlin from a business trip. Georg additionally mentions that his name was not mentioned in a commemoration volume for former professors of chemistry at the Ruprecht Karl University of Heidelberg. Georg assumes that his name was withheld on account of his Jewish heritage and expresses discontent.
Keywords: Third Reich; Jews, German; Bredig, Georg, 1868-1944; Bredig, Max Albert, 1902-1977; Chemistry